Ambulatory Blood Pressure in Relation to Plasma and Urinary Manganese. Issue 4 (April 2020) - Zhang, Zhen-Yu; Carmeli, Cristian; Ponte, Belen; Pruijm, Menno; Ackermann, Daniel; Ehret, Georg; Guessous, Idris; Petrović, Dušan; Pechère-Bertschi, Antoinette; Vogt, Bruno; Martin, Pierre-Yves; Burnier, Michel; et al.
Abstract : The association of blood pressure (BP) with manganese—an essential trace element required for human health—remains poorly studied. In 734 randomly recruited Swiss participants (mean age, 47.5 years; 51.4% women), we related ambulatory BP to 2 biomarkers, plasma manganese (pMn) and the urinary manganese (uMn) excretion. To allow for diurnal variation, we assessed BP and uMn over 24 hours and during wakefulness and sleep, using split urine samples. Twenty-four-hour, daytime, and nighttime systolic/diastolic BPs averaged 119.8/78.1, 123.8/81.2, and 107.0/68.3 mm Hg; the corresponding median uMn were 199.5, 83.0, and 51.5 μmol and median pMn, 0.52 μg/L. In analyses dichotomized by the median of the biomarkers, greater pMn was associated with higher 24-hour systolic/diastolic BP (+4.1/+2.3 mm Hg; P ⩽0.0003), greater daytime uMn with lower daytime BP (−3.5/−1.9 mm Hg; P ⩽0.0067), and greater nighttime uMn with higher nighttime BP (+2.9/+1.2 mm Hg; P ⩽0.046). In multivariable-adjusted analyses, significance ( P ⩽0.030) was retained for the positive association of 24-hour and daytime diastolic BP with pMn and for systolic BP in relation to uMn at night. The association sizes for a 2-fold increment in the biomarkers amounting to 0.77 mm Hg (95% CI, 0.08–1.47 mm Hg), 0.97 (CI, 0.20–1.76) and 1.33 (CI, 0.20–2.50 mm Hg), respectively. In conclusion, there were positive associations between diastolic BP and pMn over 24 hours and during daytime and between systolic BP and uMn at night. Abstract : Supplemental Digital Content is available in the text.